Preseason weight-bearing ankle dorsiflexion in male professional football players with and without a history of severe ankle injury: A novel analysis in an English Premier League club. (November 2021) - Clark, Nicholas C.; Campbell, Stuart D.
Abstract: Objectives: Ankle injuries are common in professional football and have profound player/team/club consequences. The weight-bearing lunge-test (WBLT) assesses ankle dorsiflexion range-of-motion in football primary/secondary injury prevention and performance contexts. Data for uninjured and previously ankle-injured players in the English Premier League (EPL) is not available. This study analysed WBLT measurements (cm) within and between uninjured and previously severe ankle-injured players (injured-stiff group, injured-lax group) in one EPL club. Design: Cross-sectional. Setting: Preseason. Participants: Forty-nine players (age 22.9 ± 4.6 yr; height 181.6 ± 5.2 cm; mass 77.7 ± 7.6 kg). Main outcome measures: Prevalence (%) of previous unilateral severe ankle injury (USAI). Side-to-side (right/left, dominant/nondominant, injured/uninjured) WBLT comparisons at group-level ( t -test [within-group]; Welch's ANOVA [between-group]; effect sizes [within-/between-group]) and individual-level (limb symmetry index [%]; absolute-asymmetry [%]). Results: Prevalence of USAI was 38.7%. There were no statistically-significant side-to-side differences for within-/between-group comparisons. Effect sizes: just-below-large (injured-stiff) and extremely-large (injured-lax) for within-group injured-side/uninjured-side comparisons; just-below-medium (injured-lax) to just-above-medium (injured-stiff) for injured-side comparisons to uninjured players. Absolute-asymmetries: uninjured players, 15.4±13.2%; injured-stiff, 21.8±33.6%; injured-lax 20.4±13.6%. Conclusions: Over one-third of players had previous USAI. Effect sizes indicate substantial within-group side-to-side differences and less substantial between-group differences. Across groups, some players had absolute-asymmetries that may elicit concern in ankle primary/secondary injury prevention and performance contexts. Highlights: Of 49 players, 19 (38.7%) had a history of unilateral severe ankle sprain (USAI). Players with USAI can be categorised into injured-stiff or injured-lax groups. Effect size analyses reveal within-group side-to-side differences were substantial. Injured groups' injured-side data deviated from established reference values. Across groups, substantial ankle dorsiflexion side-to-side asymmetry was prevalent.